Pengembangan E-Modul Case Based Learning Berbantuan Augmented Reality Untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Pada Mata Pelajaran Informatika SMP - Marcel Prastiko Arthana; I Komang Sudarma; Ni Nyoman Parwati; Ketut Agustini; I Wayan Sukra Warpala (Cetta: Jurnal Ilmu Pendidikan, 2026)
The problem of low critical thinking skills among grade VII students in informatics at SMP Negeri 4 Singaraja is closely linked to the persistent use of conventional teaching methods. These traditional approaches often lack interactivity, limiting students' understanding of abstract technical concepts like computer networks and algorithms. To address this pedagogical gap, this study aims to develop an interactive e-module based on the case based learning model, integrated with augmented reality technology to facilitate an immersive learning experience. This research and development study adopted the ADDIE instructional model and employed a one-group pretest-posttest design. Data were collected using expert validation sheets, practicality questionnaires, and higher order thinking skills oriented critical thinking tests. The effectiveness was analyzed using the N-gain index, paired sample t-tests, and Cohen’s d effect size. The results indicate that the AR based CBL e-module achieved a 100% validity score based on expert evaluations, along with excellent practicality scores of 91% from students and 100% from teachers. Furthermore, the field test showed a statistically significant improvement in students' critical thinking skills (p < 0.001) with a large effect size of 3.955, reflecting a strong positive impact on learning outcomes. In conclusion, the AR assisted CBL e-module is a highly valid, practical, and effective educational tool. This study contributes to the educational technology literature by demonstrating how integrating 3D visual scaffolding with authentic case scenarios successfully overcomes cognitive barriers and fosters higher-order thinking.